Testicular Volumes Measurement Comparison by Ultrasound and Orchidometer and Its Relationship with Nutritional Status in Transfusion-dependent Thalassemia - Rahmad Mulyadi; Joedo Prihartono; Em Yunir; Dian Anindita Lubis; Reyhan Eddy Yunus (The Indonesian Biomedical Journal, 2023)
BACKGROUND: One type of thalassemia known as transfusion-dependent thalassemia (TDT) requires a lifelong blood transfusion. Iron overload from prolonged blood transfusions causes nutritional disorders and several organs impairment, including the testicles. In contrast to an orchidometer, ultrasound shows more details of the testicles. This study aimed to compare testicular volumes based on ultrasound and orchidometer measurements and correlate testicular volume with nutritional status in TDT patients.METHODS: A cross-sectional study including 27 male thalassemia subjects who underwent routine check-ups was conducted. Measurements of testicular volume using an orchidometer and ultrasound, and body mass index (BMI) was performed. Ultrasound measurement of testicular volume was calculated using the Lambert Formula, while the orchidometer was performed by matching the bead next to the testicle.RESULTS: Most subjects were underweight (63%) or normal weight (37%). However, no significant correlation between BMI and testicular volume was found. As measured using an orchidometer, the mean volume of the right and left testes were 9.22±4.92 mL and 8.67±4.45 mL, respectively. Ultrasound measurement showed the mean values of the right and left testicles were 7.68±3.96 mL and 7.09±4.03 mL, respectively. Testicular measurements obtained using ultrasound showed a significant difference (p<0.05) when compared with the orchidometer. The testicle measured by ultrasound was smaller, which was more accurate. However, the comparison between the right and the left testicular volumes showed no significance.CONCLUSION: Thalassemia patients are mainly underweight, and their nutritional status have no relationship with testicular volume. Ultrasound, as compared to an orchidometer, is better for measuring testicular volume.KEYWORDS: thalassemia, testicle, orchidometer, ultrasound, body mass index